Occupational Risk for Coronary Artery Disease in Shift Workers – A Systematic Review - d'Ettorre, Gabriele; Piscitelli, Prisco; Pellicani, Vincenza; Tornese, Roberta; Ceccarelli, Giancarlo; d'Ettorre, Gabriella; La Torre, Giuseppe (La Medicina del Lavoro, 2024)
Background: Coronary artery disease (CAD) prevention in shift workers (SWs) poses a significant challenge worldwide, as CAD remains a major cause of mortality and disability. In the past, SWs were found at higher risk of CAD than non-s SWs. Nevertheless, the pathogenic mechanism between shift work and CAD to date is unclear. This systematic review aims to enhance understanding of the risk of CAD occurrence in SWs. Methods: A systematic literature review was conducted from January 2013 to December 2023. MEDLINE/Pubmed databases were used initially, and additional relevant studies were searched from references. Shift work was defined as any schedule outside traditional shifts, including the night shift. Results: Fifteen pertinent papers were categorized into risk assessment or risk management. Findings demonstrated an increased risk of CAD among SWs compared to non-SWs, with an increased CAD risk observed for both shift work and night shift work. Discussion: Duration-response associations indicate that greater shift exposure is linked to higher CAD risk. SWs incur an increased risk of CAD through the atherosclerotic process. As shift work duration increases as the risk of atherosclerosis is higher, workers demonstrate a higher prevalence and severity of coronary artery plaques. Conclusions: The evidence-based results underscore the increased risk of CAD in SWs and are sufficient for proposing guidelines aimed at reducing the risk of CAD in SWs and at managing people with CAD in return to work characterized by disrupted circadian rhythms.